Norwegian Air Boeing 737 MAX 8 at Helsinki Airport - Campbell, Sandy (2018)
Norwegian currently has 8 Norwegian Air Boeing 737 MAX 8s in its fleet of about 150 aircraft. One of the most identifiable characteristics of this aircraft are the "winglets" or wingtip structures which reduce drag. The aircraft seats 189 passengers and has two pilots and a 4 person cabin crew. It is more fuel efficient and quieter than older models. Norwegian Air services 29 destinations in Scandinavia (Denmark, Finland, Iceland Norway and Sweden) and has 500 routes to more than 150 cities.